(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: The aim of this study was to compare the B mode ultrasonography findings of thyroid gland and peak systolic velocity of inferior thyroid artery by color Doppler application, in patients with diffuse toxic goiter at the time of diagnosis and 6-8 months after radioiodine 131-I therapy. Patients and Methods: This was a prospective observational study conducted in National Institute of Nuclear Medicine & Allied Sciences (NINMAS) between June 2015 and October 2016. Forty consecutive diagnosed diffuse toxic goiter patients were selected at the time of diagnosis prior to radioiodine therapy. An ultrasonography evaluation of thyroid gland (measurement of anterior posterior diameter for convenience) and measurement of peak systolic velocity of inferior thyroid artery in both sides of thyroid gland were performed before and after 131-I therapy (6-8 months). The examination was performed in thyroid division of NINMAS by advanced ultrasound machine with a linear transducer (5-12 MHz). The patients were divided into two groups. Group A-diffuse toxic goiter prior to radioiodine therapy and group B- same patients 6-8 months after radioiodine therapy. Results: A reduction in the anterior –posterior diameter of the thyroid gland was observed from pre to post treatment evaluation, performed at 6 and or 8 months after radioiodine therapy. Color Doppler showed increased parenchymal vascularity at the time of diagnosis which gradually declined after radioiodine therapy. Thyroid blood flow, as assessed by PSV of ITA, was significantly higher in Group A than in Group B respectively (70.5 ± 15.5 cm/ sec versus 22.2 ± 12.9 cm/sec). PSV was measured in 10 healthy euthyroid adults & their PSV ranged 13-20 cm/Sec. Parenchymal vascularity of the thyroid gland was higher in hyperthyroid patients than in euthyroid patients. Conclusion: Assessment of thyroid gland by B-mode ultrasound and blood flow by color Doppler study (CDS) is an effective marker in the initial diagnosis of diffuse toxic goiter. Bangladesh J. Nuclear Med. 20(1): 41-44, January 2017